Final Report : Online Assessment Feedback as an Instrument of Reflective Learning Practice in Human Biology. - Meyer, Jan; Fyfe, Georgina; Fyfe, Sue; Ziman, Melanie; Hill, Julie; Sanders, Kathy; Hewitt, D.; Bennett-Chambers, Marilyn; Brightwell, R.; Plastow, Kayty; Koehler, Nicole; Sly, Leith (Carrick Institute for Learning and Teaching in Higher Education, 2008)
Final report from a project that developed an online assessment system for the improvement of evaluation of Human Biology students' higher level learning and skill development. The project team sought to address the challenge of teaching large classes, by developing a system which will provide a more sophisticated online dialogue with students and improved individual feedback mechanisms. The assessment system extends the aspects of Human Biology that can be assessed online (including laboratory exercises); provides analytical tools (including sets of exemplars and remedial materials); administers richer, more analytical feedback; and embeds reflective practice and self-performance assessment into the feedback component of the online assessment system. The project team have collaborated with partner institutions who have implemented the online assessment tool, in an effort to share evaluation and feedback and make improvements to the system.